Classroom management in improving the quality of learning in the education units - Mustafa, M. Nur; Hermandra, .; Zulhafizh, .; Hidayat, Riyan (North American Business Press, 2024)
This study focuses on classroom management in education units as a basis to improve the quality of learning. This process relates to the instruments used for data collection. The instrument consisted of thirty-five related to classroom management. The sample was 142 people who were spread in the education unit of Riau Province, Indonesia. Sampling was undertaken by random sampling in accordance with the readiness of the respondent. Data were analysed by substituting the respondents’ results through descriptive statistics, then using the Product Moment correlation method, the contribution of indicators in realizing the success of implementing learning through ANOVA. The average demographic data of the respondents was 4.273 (very high); compile a lesson plan was 4.304 (very high); carry out learning was 4.352 (very high); assess achievement was 4.233 (very high); carry out follow-up the results of the assessment of learning achievement was 3.813 (high). Quality did not vary with a very high correlation value so that it contributed a role in building class management up to 100%.